Penyelesaian Sengketa Rumah Susun Yang Masih Terikat PPJB Oleh Pengembang Nakal Yang Melakukan Wanprestasi - Tri Ayu Mulyaningsih; Devi Siti Hamzah Marpaung (Pascasarjana Ilmu Hukum, Universitas Widyagama Malang, 2022)
The high demand for housing and the lack of human income causes the construction of flats to increase, because the cost is cheaper and usually many buyers can only afford a down payment or down payment. Because the purchase cannot be carried out, the party can make a binding agreement as a preliminary agreement for the sale of flats. PPJB is carried out in a condition where the building is not completely finished, which is 20%. Sales through PPJB cause many laws that harm prospective buyers, one of the problems is facing the sale and purchase binding deed because the developer is in default. It is said to be in default because the developer did not heed the agreement. To minimize the loss of potential buyers, there must be clear and definite law enforcement that can provide justice and legal protection. The purpose of this legal research is to determine the protection aspect of land law due to default. This study uses a normative juridical legal research method with a conceptual and legal application approach to fulfill views and doctrines as the basis for legal arguments on legal issues that must be investigated. Results Based on the research, it is known that the making of PPJB for Houses/Condos made by a notary based on PERMENPUPR Preliminary System for Sale and Purchase of Houses/Sarrusun Reflects as legal certainty and the Notary is obliged to make a PPJB deed in accordance with what has been determined in PERMENPUPR Preliminary Agreement System for Sale and Purchase of Houses/Sarusun, with still refer to Article 38 of the Law on the Position of Notary and its Amendments